2006
DOI: 10.3892/or.15.5.1111
|View full text |Cite
|
Sign up to set email alerts
|

The expression of vascular endothelial growth factor determines the efficacy of post-operative adjuvant chemotherapy using oral fluoropyrimidines in stage II or III colorectal cancer

Abstract: Abstract. The aim of this study was to determine any correlation between the efficacy of post-operative adjuvant chemotherapy using oral fluoropyrimidines and the vascular endothelial growth factor (VEGF) expression in primary colorectal cancer tissues. The data were reviewed retrospectively on 342 patients with colorectal cancer at stage II or III, who underwent potentially curative resection between 1988 and 1998. Of these, 225 received post-operative administration of oral fluoropyrimidines such as UFT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Pertinent to practical decision-making, and contrary to theoretical expectation, increasing tumor vascularity does not reliably correlate with higher disease stage [112], lower chemosensitivity [113] or superior bevacizumab efficacy [114]. High serum VEGF levels suggest resistant disease and poorer prognosis [115,116]; tumor VEGF levels are more accurate predictors than serum levels [112], and correlate with lack of adjuvant fluoropyrimidine benefit for colorectal tumors [117]. Primary breast tumor cytosolic VEGF levels are inversely proportional to hormone receptor expression, and predict early relapse, but do not correlate independently with survival outcomes from conventional chemotherapy [118].…”
Section: Prediction Of Anti-vegf Treatment Benefitmentioning
confidence: 98%
“…Pertinent to practical decision-making, and contrary to theoretical expectation, increasing tumor vascularity does not reliably correlate with higher disease stage [112], lower chemosensitivity [113] or superior bevacizumab efficacy [114]. High serum VEGF levels suggest resistant disease and poorer prognosis [115,116]; tumor VEGF levels are more accurate predictors than serum levels [112], and correlate with lack of adjuvant fluoropyrimidine benefit for colorectal tumors [117]. Primary breast tumor cytosolic VEGF levels are inversely proportional to hormone receptor expression, and predict early relapse, but do not correlate independently with survival outcomes from conventional chemotherapy [118].…”
Section: Prediction Of Anti-vegf Treatment Benefitmentioning
confidence: 98%
“…This may be a reason why the ASCO does not support the use of CEA to determine whether to treat a patient with adjuvant chemotherapy. Our previous studies using stage II or III colorectal cancer [9,10] indicated that biologically aggressive tumors associated with expression of MMP-9 or VEGF were less responsive to oral fluoropyrimidine based postoperative chemotherapy compared with those without expression of MMP-9 or VEGF. In contrast, oral fluoropyrimidine based adjuvant chemotherapy significantly reduced the risk to postoperative recurrence and to death even after stratifying to the preoperative CEA level, suggesting that elevated preoperative CEA level may be predicting for benefit from postoperative adjuvant therapy in stage II disease.…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…With regard to node dissection, current recommendations are that at least 10-15 nodes be assessed [7,8]. We have previously reported that some biologic markers such as the expression of vascular endothelial growth factor (VEGF) and matrix metalloproteinase (MMP) 9 are factors that predict a worse prognosis in stage II or III colorectal cancer [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…15,18,19 VEGF-A expression in colorectal tissue, determined immunohistochemically, has also been found to be a predictive marker of the response of colorectal cancer to preoperative radiotherapy 20 and adjuvant chemotherapy. 21 A relationship between the concentration of VEGF-A in serum or cancer tissue and the progression of disease has been reported. This relationship is seen in patients with breast, gastric, hepatocellular, lung, and colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%